Status of dental health in chemical warfare victims: The case of Isfahan, Iran - Ahmad Mottaghi; Abolfath Hoseinzade; Elham Zamani; Habib Allah Araghizade (Wolters Kluwer Medknow Publications, 2012)
Background: Little evidence is available regarding the dental health of victims of chemical warfare in Iran. Therefore, in this study, we examined the decayed, missing, and filled teeth index (DMFT), community periodontal index of treatment needs (CPITN), and saliva secretion rate of chemical warfare victims living in the province of Isfahan in Iran. Materials and Methods: This case-control study was conducted with 300 chemical warfare victims as the treatment group and 300 age-matched individuals without exposure to chemical warfare as the control group. DMFT and CPITN indices and saliva secretion rate were measured and compared between the two groups. Results: Chemical warfare victims had significantly higher scores than the control group for decayed teeth (4.25±3.88 vs 3.52±2.81; P=0.009), missing teeth (8.79±9.3 vs 6.15±8.43; P<0.001), total DMFT index (17.00±6.72 vs 13.20±6.89; P<0.001), and CPTIN (2.81±0.81 vs 1.71±1.04; P<0.001). However, no significant difference was observed between the two groups in filled teeth (4.00±4.2 vs 3.59±2.48; P=0.148). The level of saliva secretion in warfare victims was significantly lower than that in the control group (1.71±0.05 vs 3.85±1.95 cc/5 min; P<0.001). Conclusion: Chemical warfare victims have relatively poor dental/oral health. Chemical injury might cause a dysfunction in saliva secretion, with decrease in saliva secretion increasing the risk for tooth decay and periodontal disorders. Further research is required to find out the exact underlying mechanisms and the factors associated with poor dental/oral health in chemical warfare victims.